1994
DOI: 10.1007/bf00402225
|View full text |Cite
|
Sign up to set email alerts
|

Topical FK506: suppression of allergic and irritant contact dermatitis in the guinea pig

Abstract: Topical FK506 has recently been shown to have an anti-inflammatory effect in vivo in humans. In this study its effects in contact dermatitis were studied in the guinea pig model. Topical FK506 suppressed both irritant and allergic patch-test reactions. The most prominent suppressive effect was seen when skin sites were pretreated with FK506. Topical FK506 did not impair the induction of contact allergy as assessed by challenges, although it suppressed local lymph node cell accumulation during contact allergy i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…The structure and barrier properties of the skin in man are well known to resemble those in guinea pigs more than those in mice. In addition, guinea pigs are reported to be relatively resistant to steroids [11], and, except for steroids and some immunosuppressive agents such as cyclosporin A [12, 13]and FK-506 [14], few compounds are known to have suppressive effects against CHR in guinea pigs by topical application [15]. Taken together, the data would suggest CX-659S to be an effective topical drug for the treatment of cutaneous disorders in humans.…”
Section: Discussionmentioning
confidence: 85%
“…The structure and barrier properties of the skin in man are well known to resemble those in guinea pigs more than those in mice. In addition, guinea pigs are reported to be relatively resistant to steroids [11], and, except for steroids and some immunosuppressive agents such as cyclosporin A [12, 13]and FK-506 [14], few compounds are known to have suppressive effects against CHR in guinea pigs by topical application [15]. Taken together, the data would suggest CX-659S to be an effective topical drug for the treatment of cutaneous disorders in humans.…”
Section: Discussionmentioning
confidence: 85%
“…Allergic contact dermatitis is responsive to topical FK-506 as well. The efficacy in this condition was reported in humans [21] and further investigated in guinea pig [22]. Whether topical FK-506 is also effective in psoriasis vulgaris remains to be verified.…”
Section: Clinical Application In Dermatologymentioning
confidence: 91%
“…Animal model studies (guinea pigs and pigs) have shown topical tacrolimus to be effective in the prevention and the treatment of acute allergic and irritant contact dermatitis. 16,17 In a human study, topical tacrolimus (at concentrations of 0.01%, 0.1%, and 1%) in ethanol and ethanol alone were applied to 5 volunteers for 48 hours. 1-Chloro-2,4-dinitrobenzene (DNCB) was then applied to the skin.…”
Section: Acute Contact Dermatitismentioning
confidence: 99%